Understanding the Victimization-Delinquency Overlap Among Latino Adolescents: The Role of Cultural and Mental Health Factors - Cuevas, Carlos A. (Journal of interpersonal violence, 2022)
The aim of this analysis was to evaluate whether cultural factors and mental health variables distinguish Latino youth who are delinquent-victims, primarily victims, or primarily delinquent. This study used data from the Dating Violence among Latino Adolescents (DAVILA) Study, which surveyed 1,525 Latino youth and queried participants about past year victimization, delinquency, psychological distress, and cultural factors. Using multinomial logistic regression, we evaluated whether these variables differentiated youth who were delinquent-victims, primarily victims, primarily delinquent, or neither delinquent nor victims. Results suggest that delinquent-victim Latino youth are differentiated from other groups primarily by the degree of familial support and anger/hostility. Other cultural and mental health variables do not appear to differentiate the groups, suggesting a greater degree of similarity among them based on the variables used in the analysis. The results indicate that Latino youth that are victimized and engage in delinquent behavior are primarily differentiated by the degree of anger/hostility they experience. Familial support, as has been seen with non-Latino groups, appears to present a significant protective quality and likely can serve as a prevention strategy, particularly for delinquent-victim youth. Study limitations include challenges with retrospective self-report and sampling using RDD methodologies.